Reflections on the present state of economics - STEINDL, J. (PSL Quarterly Review, 2013)
The paper is a contribution to a series of recollections and reflections on the professional experiences of distinguished economists which the Banca Nazionale del Lavoro Quarterly Review started in 1979. In it Josef Steindl recalls the major advents in the field of economics and his own work and life to reflect on the state of today’s economics. JEL: B31, A11